Migrantki jako kreatorki własnego życia = Women migrants as creators of their own life - Krasnodębska, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the presented text on migratory women, migration was shown as an important factor in innovation and transgressive activities. The aim of the study was to explore the openness of women migrants to new experiences. The results of the survey show that before taking the decision to migrate, the women had been characterized by productive thinking generated by new, frequently dramatic life situations (lack or loss of job, debt, etc.). Such situations led those women to risk atypical actions that could bring positive effects. The migratory stay itself contributed to changes in their thinking about the world, changing their beliefs, building new roles in the family and the professional area. It was revealed that migrant women attempted to control their emotional states, develop character traits and self-knowledge. It may be stated thus that migration contributed to their "emancipatory transgression".
Keywords: kobiety; migracja; praca; rodzina; transgresja; women; migration; work; family; transgression